The pathogenicity characterization of non-O1 Vibrio cholerae and its activation on immune system in freshwater shrimp Macrobrachium nipponense. Issue 87 (April 2019) - Li, Xixi; Yang, Hui; Gao, Xiaojian; Zhang, Honghua; Chen, Nan; Miao, Zhen; Liu, Xiaodan; Zhang, Xiaojun
Abstract: Outbreaks of mass mortalities among cultured Macrobrachium nipponense occurred in a commercial hatchery during the autumn of 2017 in Jiangsu province, P. R. China, and non-O1 Vibrio cholerae was isolated and identified as causal agents of M. nipponense, with a LD50 value 4.09 × 10 4 CFU/mL. Detection of virulence-associated genes by PCR indicated that XL1 was positive for Mp, HlyA, RtxA, OmpU, Ace, Zot and T6SS . Furthermore, the results of extracellular enzyme analysis revealed that the strain can produce lecithinase, amylase, gelatinase and hemolysin. Histopathological analysis revealed that the hepatic tubule lumen and the gap between the hepatic tubules became larger, and the brush border disappeared in the hepatopancreas. Quantitive real-time PCR (qRT-PCR) was undertaken to measure mRNA expression levels for thirteen immune related genes in M. nipponense after non-O1 V. cholerae infection. The transcriptional analysis of these immune related genes demonstrated that the expression levels of dorsal, relish, p38, crustin1, crustin2, crustin3, hemocyanin, i-lysozyme, anti-lipopolysaccharide factors 1, anti-lipopolysaccharide factors 2, prophenoloxidase were significantly up-regulated in hemolymph of M. nipponense post-infection. These results revealed varying expression profiles and clear transcriptional activation of these immune related genes in hemolymph, which will contribute to better understand the pathogenesis and host defensive system in non-O1 V. cholerae invasion. Highlights: Mass mortalities of cultured Macrobrachium nipponense from several farms in Yangzhou city of China is reported. Non-O1 Vibrio cholerae XL1 carry Mp, HlyA, RtxA, OmpU, Ace, Zot and T6SS by PCR detection. Non-O1 Vibrio cholerae triggers a wide defensive response of various immune related genes in Macrobrachium nipponense.